Glocal Traction Control for In-wheel-motor Electric Vehicles - A Passivity Approach -. Issue 2 (2020) - Nguyen, Binh-Minh; Tsumura, Koji; Hara, Shinji
Abstract: Although traction control of in-wheel-motor electric vehicles (IWM-EVs) has been studied for years, we still face the essential theoretical issue: How to assure the stability of the overall system while attaining both global and local control performances? This issue has been neglected by almost the works in the literature. The main reason is due to the nonlinearity and complexity in vehicle dynamics, especially the vehicle driven by multi-actuators. A new traction method is proposed in this paper in the glocal (global/local) framework to overcome this problem. The command to each local IWM includes two signals: (i) the local signal through anti-slip control in the lower-layer, and (ii) the global signal distributed from the driver or the upper-layer controller that managing the average wheel velocity. Stability of the whole system is guaranteed based on the fundamental passivity theory. The effectiveness of the proposed approach is verified by using Carsim/Matlab co-simulator.